The Role Of Social Trust In Purchasing Decisions Within The Online Reseller Ecosystem - Anila Dani Sakinah (PAPUA: International Journal of Sharia Business Management, 2025)
This study investigates the pivotal role of social trust in influencing consumer purchasing decisions within the online reseller ecosystem, a decentralized and community-driven digital marketplace that is especially prominent in Southeast Asia. While existing literature primarily emphasizes platform or institutional trust, this research shifts focus to interpersonal trust cultivated through peer interaction, testimonial networks, and community presence. Utilizing a qualitative research approach, the study collected data from 15 purposively selected participants—active consumers of online resellers through platforms such as Shopee, Instagram, and WhatsApp groups. Thematic analysis was employed to interpret the narratives, focusing on recurring patterns in how trust is constructed. The findings reveal four core dimensions of social trust: (1) peer testimonials and social proof significantly influence perceived credibility; (2) frequent and empathetic communication fosters relational confidence; (3) transparency and honesty in product information reduce perceived risk; and (4) a reseller’s visibility and reputation within digital communities function as a social safety net. The research also suggests expanding theoretical models to include social capital and network-based trust for more nuanced understanding. Practical implications are offered for online resellers and policymakers to enhance trust-building mechanisms in digital commerce environments.